MANAJEMEN GURU BIMBINGAN KONSELING DALAM MEMBENTUK KARAKTER ANTI BULLYING SISWA DI MAN 1 GRESIK - Nur Laily Agustin; Muttaqin Habibullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying is a serious problem that still frequently occurs in school settings and can have a negative impact on students’ psychological well-being. This study aims to examine how Guidance and Counseling (BK) teachers manage the development of students’ anti-bullying character at MAN 1 Gresik. This study employs a qualitative method, utilizing data collection techniques such as interviews and observations of BK teachers and students. The results indicate that Guidance and Counseling teachers foster anti-bullying character through collaboration among the entire school community, utilizing programs such as group counseling, awareness campaigns, BK teachers implement systematic steps ranging from information gathering to mediation. However, it was still found that students consider teasing to be a common occurrence and tend not to report bullying incidents. Therefore, strengthening character building, increasing student awareness, and fostering a safe and open school environment are necessary so that bullying prevention efforts can be more effective.